Are the effects of APOE ϵ4 on cognitive function in nonclinical populations age- and gender-dependent?. (February 2015) - Rusted, Jennifer; Carare, Roxana O
SUMMARY : APOE ϵ4 – one of three possible allelic variants (ϵ2, ϵ3 and ϵ4) of the polymorphic protein APOE – is well characterized in its role as the strongest risk factor (after old age) for sporadic Alzheimer's disease (AD). Perhaps less well known, and certainly less well characterized, is that this ϵ4 variant of the APOE gene also is a significant risk factor for age-related cognitive decline in nonclinical populations. This article considers APOE ϵ4 effects on cognition in people without dementia, the extent to which such effects may depend on age and on gender and other interactive biological systems that change across the lifespan.